Pseudorabies - Schoneweis, D.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pseudorabies has been talked and written about so much the last few years that it seems that there isn't anything left to be said. It may be that so much has been said about the disease that now is the time to review the disease as it relates to Kansas swine producers. First of all, I'd like to discuss briefly two factors that need to be clarified: (1), pseudorabies is not to be confused with rabies--there are no recorded instances of humans being affected by the virus; and (2), pseudorabies is not a new disease. First reported in scientific literature by Aujeszky in 1902, Aujeszky's disease is one of its synonyms. A review of the literature published in this country suggests that pseudorabies has been a problem at least as far back as 1813. It has now become a big problem in the swine industry. Pseudorabies is caused by a herpes virus. A fairly resistant virus, it can persist in bedding for 10 days at 75 F. or for 30 days at 65 ̊ F., and on a wooden floor for 7 weeks. It can survive for 6 months at 38 F. The virus can be destroyed by most disinfectants if properly applied.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Pseudorabies